Diagnostic performance of CT scan–based radiomics for prediction of lymph node metastasis in gastric cancer: a systematic review and meta-analysis - HajiEsmailPoor, Zanyar; Tabnak, Peyman; Baradaran, Behzad; Pashazadeh, Fariba; Aghebati-Maleki, Leili (Frontiers in Oncology, 2023)
The purpose of this study was to evaluate the diagnostic performance of computed tomography (CT) scan-based radiomics in prediction of lymph node metastasis (LNM) in gastric cancer (GC) patients.Methods: Pubmed, EMBASE, Web of Science and Cochrane Library databases were searched for original studies published until November 10, 2022 and the studies satisfying the inclusion criteria were included. Characteristics of included studies and radiomics approach and data for constructing 2×2 tables were extracted. The Radiomics Quality Score (RQS) and Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) were utilized for the quality assessment of included studies. Overall sensitivity, specificity, diagnostic odds ratio (DOR), and area under the curve (AUC) were calculated to assess diagnostic accuracy. The subgroup analysis and spearman's correlation coefficient was done for exploration of heterogeneity sources.Results: Fifteen studies with 7010 GC patients were included. We conducted analyses on both radiomics signature and combined (based on signature and clinical features) models. The pooled sensitivity, specificity, DOR, and AUC of radiomics models compared to combined models were 0.75 (95% CI, 0.67-0.82) vs. 0.81 (95% CI, 0.75-0.86), 0.80 (95% CI, 0.73-0.86) vs. 0.85 (95% CI, 0.79-0.89), 13 (95% CI, 7-23) vs. 23 (95% CI, 13-42), 0.85 (95% CI, 0.81-0.86) vs. 0.90 (95% CI, 0.87-0.92), respectively. The meta-analysis indicated a significant heterogeneity among studies. The subgroup analysis revealed that arterial phase CT scan, tumoral and nodal region of interest (ROI), automatic segmentation and 2D ROI could improve diagnostic accuracy compared to venous phase CT scan, tumoral only ROI, manual segmentation and 3D ROI, respectively. Overall, the quality of studies was quite acceptable based on both QUADAS-2 and RQS tools.CT scan-based radiomics approach has a promising potential for the prediction of LNM in GC patients preoperatively as a non-invasive diagnostic tool. Methodological heterogeneity is the main limitation of the included studies.